Pragmatic Equivalence of Phatic Utterance in the Indonesian Translation of Pride and Prejudice Novel by Jane Austen - Kasanah, Alimah Nur; Sajarwa, Sajarwa (Publikasi Indonesia, 2025)
This research explores how phatic utterances, which are important for social interaction in Jane Austen's Pride and Prejudice, are translated into Indonesian. These expressions are challenging to translate because of cultural and language differences, especially when trying to keep their social and emotional meaning. This study identifies types of phatic expressions, looks at the translation methods used in the Mizan Indonesian version, and checks how well the original meaning is kept. It uses a descriptive qualitative approach, comparing dialogues from the English original and the Indonesian translation. The study uses theories on phatic communication (Malinowski, 1923; Jakobson, 1960), translation strategies (Baker, 2018), and pragmatic equivalence (Baker, 1992; Searle, 1969), focusing on what's implied, assumed, and intended. The analysis shows that the translator used several methods. “Cultural substitution